PENGARUH ANALISIS JABATAN, REKRUTMEN DAN SELEKSI KARYAWAN TERHADAP KINERJA KARYAWAN TETAP NON PNS - Nilawati Fiernaningsih; Pudji Herijanto; Musthofa Hadi (Adbis: Jurnal Administrasi dan Bisnis, 2018)
Every educational organization, HR has a very important role because HR is the determinant of the success or failure of the organization in achieving organizational goals. In order for organizational goals to be achieved, it is necessary to have job analysis, employee recruitment and employee selection so that the organization can get employees who perform optimally. This study aims to determine the effect of job analysis, employee recruitment and selection on employee performance. This research was conducted at the State Polytechnic of Malang with a population of 565 non-civil servant permanent employees and a sample of 135 people taken randomly. The analysis technique used is SEM by using the AMOS 16 application. The results of the study concluded that job analysis, recruitment and selection of employees affect performance.